Identification of cellular factors required for the budding of koala retrovirus. (16th July 2013) - Shimode, Sayumi; Nakaoka, Rie; Hoshino, Shigeki; Abe, Masumi; Shogen, Hiroko; Yasuda, Jiro; Miyazawa, Takayuki
ABSTRACT Koala retrovirus (KoRV) is a unique gammaretrovirus that is currently endogenizing into its host and considered to be associated with leukemia, lymphoma and immunosuppression in koalas (Phascolactos cinereus). In this study, it was demonstrated that WWP2 or WWP2‐like E3 ubiquitin ligases possessing the WW domain closely related to WWP2 and Vps4A/B are involved in KoRV budding. These data suggest that KoRV Gag recruits the cellular endosomal sorting complex required for transport machinery through interaction of the PPPY L‐domain with the WW domain(s) of WWP2 and that progeny virions are released from cells by utilizing the multivesicular body sorting pathway.